Genome-wide association study of letrozole plasma concentrations identifies non-exonic variants that may affect CYP2A6 metabolic activity - Hertz, Daniel L. (Pharmacogenet Genomics, 2021)
OBJECTIVE: Letrozole is a non-steroidal aromatase inhibitor (AI) used to treat hormone receptor positive (HR+) breast cancer. Variability in letrozole efficacy and toxicity may be partially attributable to variable systemic drug exposure, which may be influenced by germline variants in the enzymes responsible for letrozole metabolism including Cytochrome P450 2A6 (CYP2A6). The objective of this genome-wide association study (GWAS) was to identify polymorphisms associated with steady state letrozole concentrations. METHODS: The Exemestane and Letrozole Pharmacogenetics (ELPh) Study randomized post-menopausal patients with HR+ non-metastatic breast cancer to letrozole or exemestane treatment. Germline DNA was collected pre-treatment and blood samples were collected after 1 or 3 months of treatment to measure steady-state letrozole (and exemestane) plasma concentrations via HPLC/MS. Genome-wide genotyping was conducted on the Infinium Global Screening Array (>650,000 variants) followed by imputation. The association of each germline variant with age- and body mass index-adjusted letrozole concentrations was tested in self-reported white patients via linear regression assuming an additive genetic model. RESULTS: There were 228 patients who met the study specific inclusion criteria and had both DNA and letrozole concentration data for this GWAS. The association for one genotyped polymorphism (rs7937) with letrozole concentration surpassed genome-wide significance (p=5.26x10(−10)), explaining 13% of the variability in untransformed steady-state letrozole concentrations. Imputation around rs7937 and in silico analyses identified rs56113850, a variant in the CYP2A6 intron that may affect CYP2A6 expression and activity. rs7937 was associated with age- and body mass index-adjusted letrozole levels even after adjusting for genotype-predicted CYP2A6 metabolic phenotype (p=3.86x10(−10)). CONCLUSIONS: Our GWAS findings confirm that steady-state letrozole plasma concentrations are partially determined by germline polymorphisms that affect CYP2A6 activity, including variants near rs7937 such as the intronic rs56113850 variant. Further research is needed to confirm whether rs56113850 directly affects CYP2A6 activity and to integrate non-exonic variants into CYP2A6 phenotypic activity prediction systems.